Pengaruh Reward terhadap Prestasi Kerja Guru di Yayasan Sekolah Albanna Denpasar Tahun Pelajaran 2019/2020 - Hasanat Uzzahroh, Umi; Sudarsono, Sudarsono; Rusmayani, Rusmayani (STAI Denpasar Bali, 2022)
Rewarding high-achieving teachers will motivate teachers to further increase their productivity in work. The performance of the work is the result of the quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The purpose of this research is to know: 1) The effect of reward on teacher work performance in Yayasan Sekolah Albanna Denpasar 2) Large contribution of reward to teacher's work performance at Yayasan Sekolah Albanna Denpasar. The method in this study uses quantitative research korelational. The data collection techniques used are using questionnaires, observations and documentation. The sample is determined by the slovin formula and obtained as many as 107. The data is analyzed with a simple regression that was previously preceded by a prerequisite analysis test. The results showed 1) there was a positive and significant influence on teacher employment performance. This is indicated by Y= 47,334+0.525X which means if the reward variable increases by 1 point then there will be an increase in the reward of 0.525. Judging by the F test known Fcount is 65,334 smaller than the Ftable of 4.23 with a significant < 0.05, i.e. 0.000 greater than 0.05.,. This means Ho is rejected and Ha is accepted. 2) reward variables contributed 37.7% to teacher achievement variables and the remaining 62.3%were influenced by other factors not studied by the authors.